FRENCH FEMINISM: J. KRISTEVA’S INTELLECTUAL AGENCY - Shockett, Enkelena S (Acta Scientiae et Intellectus, 2024)
In this article I will point out the intellectual agency of Julia Kristeva as a very important voice in the realm of French Feminist Studies and beyond (Feminist Theory, Critique of Identity, Psychoanalysis, Socialist Realism). At this point I will provide an exposè of her contribution in the conceptualization of Écriture feminine proposing the concept of intertextuality to explain the interconnectedness of all aspects of communication synthesizing a new methodology bestowed to us as semanalysis. It was out of this analysis that she produced and developed the concept of chora, which in itself remains a pre-linguistic and pre-subjective realm of psychosexual development. Further more, I intent to transmit that J. Kristeva’s logic approaches a product built - up as identity and as such to reason out the identity conceptualization we unquestionably proceed with its connotative evaluation in its meaningful totality. In addition, I will also explore how her concepts find room in Socialist Realism developed in the Communist Albania.